Relationship between thermo-hygrometric variations and the maturity of dates in Biskra (Case of Deglet Nour) - Mohammed Faci (Presses Agronomiques de Gembloux, 2021)
Variations in climatic conditions have direct impacts on plant growth and crop yields, both in quality and quantity. In recent years, many studies have proven the hypothesis of global warming. In the context of climate change, the study of the behavior of cultivated plants has become a necessity, in order to guarantee the food security of the populations. Our contribution focuses on the influence of temperature and relative air humidity on the development cycle of Deglet Nour dates in Biskra. To achieve our objectives, we followed the phenological cycle of the date palm, cultivar Deglet Nour, for two years (2018 and 2019). At the same time, thermo-hygrometric recorders were installed inside the palm groves of Lichana and El-Kantara. Finally, we calculated the thermal accumulation and the time required for the dates to ripen. Deglet Nour dates, in the wilaya (province) of Biskra, require a thermal accumulation of approximately 3450-4250°C to ripen, equivalent to 30-44 weeks. The results show that air temperatures and humidity have been trending upwards. The dates of the appearance and opening of the spathes have become earlier and the same for the maturity of the fruits.